Manipulated Stocks and Corruption: Lessons from Three Indonesian Verdicts - Henry Chevalier; Benny Sumardiana; Waspiah Waspiah (Journal of Law and Legal Reform, 2025)
The Jiwasraya, Asabri, and DP4 cases are major financial scandals in Indonesia involving stock price manipulation and corruption. These crimes stemmed from weaknesses in capital market regulations, weak oversight, and conflicts of interest in the management of investment funds in state financial institutions. The perpetrators exploited regulatory loopholes to divert funds into low-quality stocks whose prices were manipulated through fraudulent transactions and misleading information. The state losses, reaching hundreds of trillions of rupiah, underscore the need for financial governance reform and regulatory strengthening. The legal verdicts in these cases have a deterrent effect, with severe penalties for perpetrators, including life imprisonment and the confiscation of assets. Furthermore, capital market regulations have been tightened, a risk-based oversight system has been implemented, and transparency in the management of public funds has been increased. To prevent similar crimes, stricter oversight of investments by state-owned insurance companies and pension funds, increased transparency in financial reporting, and synergy between institutions in financial law enforcement are needed. Stronger regulatory measures can curb stock price manipulation linked to corruption, thereby restoring trust in the capital market and the national financial system.